2019
DOI: 10.3390/ph12020057
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of In Vitro Metabolism Models to PET Radiotracer Development: Prediction of In Vivo Clearance in Rats from Microsomal Stability Data

Abstract: The prediction of in vivo clearance from in vitro metabolism models such as liver microsomes is an established procedure in drug discovery. The potentials and limitations of this approach have been extensively evaluated in the pharmaceutical sector; however, this is not the case for the field of positron emission tomography (PET) radiotracer development. The application of PET radiotracers and classical drugs differs greatly with regard to the amount of substance administered. In typical PET imaging sessions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…These distinctions were also apparent in the relatively rapid clearance ( t 1/2 ) in liver microsomes. Faster plasma clearance may benefit PET imaging of the parent binding in the brain by minimizing its plasma signals, provided no brain-penetrant radiometabolites are generated. , …”
Section: Results and Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These distinctions were also apparent in the relatively rapid clearance ( t 1/2 ) in liver microsomes. Faster plasma clearance may benefit PET imaging of the parent binding in the brain by minimizing its plasma signals, provided no brain-penetrant radiometabolites are generated. , …”
Section: Results and Discussionmentioning
confidence: 82%
“…Faster plasma clearance may benefit PET imaging of the parent binding in the brain by minimizing its plasma signals, provided no brain-penetrant radiometabolites are generated. 11,20 In vitro/in vivo MetID studies were conducted to investigate the potential for brain penetration of any human-relevant radiometabolites (Figures S2 and S3 and Tables S1 and S2). In human microsomes, the metabolism of 11 was complex (17 metabolites detected), but most metabolites were of low abundance (Figure S3 and Table S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The measured values for J2 were 76.2% and 82.7% when treated with 0.5 μg/mL and 5 μg/mL, respectively, and those for NA49 were 146.6% and 101.4%. This indicates that the half-life values of J2 and NA49 can be predicted to be about 3 h and longer than 6 h, respectively ( Table 2 ) [ 38 ]. The differences in plasma stability and predicted half-life between J2 and NA49 can be attributed to the removal of a hydroxyl group at the C-5 position of the chromen-4-one ring in the metabolic pathway of NA49.…”
Section: Resultsmentioning
confidence: 99%
“…Although microsomes are considered a less physiologically relevant model than hepatocytes due to the lack of cellular organization, they are still a valuable tool for clearance determination of compounds that are metabolized primarily by phase I enzymes and that do not act as transporter substrates. Results from previous studies showed that xanthine-derived A1AR ligands are metabolized primarily by hepatic P450 enzymes [9] and that scaled microsomal clearance data are in good agreement with measured in vivo clearance [10]. Against this background, hepatic microsomes were preferred over hepatocytes for investigating species differences in A1AR ligand metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…All compounds listed in Table 1 were synthesized and characterized in our laboratories according to the procedures described in [ 4 , 10 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%